SURABAYA FRISHAPP: KOTA TERAPUNG MASA DEPAN DENGAN DESAIN âFLOATING RING SHAPED PLATEâ - Wiyono, Puput; Putra, Rigan Satria Asmara; Pratiwi, Titis Wahyu (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Based on data collected by Indonesian Maritime Magazine, in year 2030 Indonesia will lose about 2,000 islands due to global warming. While the average rate of population growth in Indonesia reaches 6% per year, this results in the amount of land to be used also diminishing. Therefore we need a solution that can overcome these problems. Reclamation is often the answer to these problems. Yet, it results in damage to the marine ecosystem. Surabaya Frishapp a floating city concept that uses the concept of